Regulation of amino acid and nucleotide metabolism by crustacean hyperglycemic hormone in the muscle and hepatopancreas of the crayfish Procambarus clarkia. - Wenfeng Li; Kuo-Hsun Chiu; Chi-Ying Lee (PLoS ONE)
To comprehensively characterize the metabolic roles of crustacean hyperglycemic hormone (CHH), metabolites in two CHH target tissues of the crayfish Procambarus clarkii, whose levels were significantly different between CHH knockdown and control (saline-treated) animals, were analyzed using bioinformatics tools provided by an on-line analysis suite (MetaboAnalyst). Analysis with Metabolic Pathway Analysis (MetPA) indicated that in the muscle Glyoxylate and dicarboxylate metabolism, Nicotinate and nicotinamide metabolism, Alanine, aspartate and glutamate metabolism, Pyruvate metabolism, and Nitrogen metabolism were significantly affected by silencing of CHH gene expression at 24 hours post injection (hpi), while only Nicotinate and nicotinamide metabolism remained significantly affected at 48 hpi. In the hepatopancreas, silencing of CHH gene expression significantly impacted, at 24 hpi, Pyruvate metabolism and Glycolysis or gluconeogenesis, and at 48 hpi, Glycine, serine and threonine metabolism. Moreover, analysis using Metabolite Set Enrichment Analysis (MSEA) showed that many metabolite sets were significantly affected in the muscle at 24hpi, including Ammonia recycling, Nicotinate and nicotinamide metabolism, Pyruvate metabolism, Purine metabolism, Warburg effect, Citric acid cycle, and metabolism of several amino acids, and at 48 hpi only Nicotinate and nicotinamide metabolism, Glycine and serine metabolism, and Ammonia recycling remained significantly affected. In the hepatopancreas, MSEA analysis showed that Fatty acid biosynthesis was significantly impacted at 24 hpi. Finally, in the muscle, levels of several amino acids decreased significantly, while those of 5 other amino acids or related compounds significantly increased in response to CHH gene silencing. Levels of metabolites related to nucleotide metabolism significantly decreased across the board at both time points. In the hepatopancreas, the effects were comparatively minor with only levels of thymine and urea being significantly decreased at 24 hpi. The combined results showed that the metabolic effects of silencing CHH gene expression were far more diverse than suggested by previous studies that emphasized on carbohydrate and energy metabolism. Based on the results, metabolic roles of CHH on the muscle and hepatopancreas are suggested: CHH promotes carbohydrate utilization in the hepatopancreas via stimulating glycolysis and lipolysis, while its stimulatory effect on nicotinate and nicotinamide metabolism plays a central role in coordinating metabolic activity in the muscle with diverse and wide-ranging consequences, including enhancing the fluxes of glycolysis, TCA cycle, and pentose phosphate pathway, leading to increased ATP supply and elevated protein and nucleic acid turnovers.